Identify the correct steps used to prove the formula ∑nj= 1(aj− aj−1)= an− a0∑j= 1n(aj− aj−1)= an− a0 , where {an} is a sequence of real numbers. (Check all that apply.)Check All That Apply1: The explicit form of the summation is∑nj= 1(aj− aj− 1) = a1− a0+ a2− a1+ a3− a2+ ...+ an− an− 12. The explicit form of the summation is∑nj= 1(aj− aj− 1) = a1− a0+ a2− a1+ a3− a2+ ... + an− an− 23. Simplifying, we get –a0 + (a1 – a1) + (a2 – a2) + .....+ (an – 1 – an – 1) + an = an – a04. Simplifying, we get –a0 + (a1 – a2) + (a2 – a1) + .....+ (an – 1 – an – 2) + an = an – a